Capturing interprofessional collaboration between physicians and nurses in an acute care setting. A validation study of the revised German version of the Collaborative Practice Scales. Issue 2 (3rd March 2020) - Rettke, Horst; Lehmann, Anja I.; Brauchli, Rebecca; Bauer, Georg F.; Petry, Heidi; Spirig, Rebecca
ABSTRACT: The relevance of interprofessional collaboration (IPC) is widely acknowledged. Given the lack of a fully validated instrument in the German language for measuring the level of IPC, we built upon the current, albeit psychometrically weak, German-language version of the instrument to devise a new version with improved wording and for subsequent psychometric testing. In a tertiary hospital in German-speaking Switzerland, 160 physicians and 374 nurses completed the revised Collaborative Practice Scales in German (CPS-G) and additional scales regarding positive and negative activation at work and regarding job demands and job resources. A confirmatory factor analysis of the CPS-G was performed, and internal consistency estimates were computed. Partial correlations between the CPS-G and the additional scales were examined for criterion validity. The model fit of the CPS-G was good for physicians (χ 2 /df = 2.38, p < .001; CFI = .923; RMSEA = .051, 90%-CI (0.037–0.065)) and moderate for nurses (χ 2 /df = 5, p < .001; CFI = .919; RMSEA = .087, 90%-CI (0.072–0.102)) supporting the two-factor structure of the original English version. Reliability was acceptable in all sub-scales for physicians (inclusion, α = 0.79; consensus, α = 0.80) and nurses (assertiveness, α = 0.77; understanding α = 0.82). As expected, the CPS-G physicians' subscales correlated positively with positive activation and job resources and negatively with negative activation and job demands, albeit not always statistically significantly. Similar correlations were found with the CPS-G nurses' subscales other than in one instance. The CPS-G showed good construct and criterion validity and acceptable internal consistency. It consequently represents a valid instrument ready for application to measure the level of interprofessional collaboration between nurses and physicians in acute care settings.